Alchemilla vulgaris and Filipendula ulmaria Extracts as Potential Natural Preservatives in Beef Patties - Khadijah Husna, Abd Hamid; Nurul Aini, Mohd Azman; Shalyda, Md Shaarani; Norashikin, Mat Zain; Normazlinah, Ahmad; Ahmad Ziad, Sulaiman; Syed Mohd Saufi, Tuan Chik; Wan Faizal, Wan Ishak; Pablos, Maria Pillar Almajano (Universiti Kebangsaan Malaysia, 2017)
Alchemilla vulgaris (AV) and Filipendula ulmaria (FU) are European medicinal plants possess bioactive compounds that exhibit many pharmacological benefits in human. The present work aims to assess two plants ethanolic extract; AV and FU of their antioxidant activities as natural preservative in beef patties. All plant samples were analysed using total polyphenol content (TPC), their antioxidant activities using Trolox Equivalent Antioxidant Capacity (TEAC), Ferric Reducing Antioxidant Power (FRAP), color and TBARS (Thiobarbituric acid reactive substances) analysis to measure their potential as synthetic preservative in muscle food. The antioxidant activity of FU and AV extracts measured with TEAC were 88.46 and 68.21 mmol of Trolox (TE)/g Dry Weight (DW) respectively. Whereas, FRAP assay were 44.6 and 40.12 mmol of TE/g DW for FU and AV extracts. The effect of lipid oxidation of beef patties were measured with adding 0.1% (w/w) of lyophilise FU and AV and Butylated hydroxytoluene (BHT) packed in modified atmosphere (MAP) (80% v/v O2 and 20% v/v CO2) for 14 days storages. FU and AV treated samples showed no significant different compared with BHT (p>0.05). Beef patties treated with 0.1% (w/w) FU showed minimum changes in red color and formation of metmyoglobin throughout storages (p<0.05). These results indicate that these edible plants extract are promising sources of natural antioxidants and can potentially be used as functional preservatives in meat products.